APLIKASI CERTAINTY FACTOR PADA AKUISISI PENGETAHUAN PENYAKIT KEJIWAAN SKIZOFRENIA - Komala, Lucy; Lubis, Chairisni (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Data aquicition is the most important component in Expert System Development. In this recearch, we used Certainty Factor for data aquicition. Data obtained will be used for establish rules, then the rules would be the value calculated in advance using the method of certainty factor. Calculations with certainty factor have a value MB, MD, and CF. After the value of MB, MD, and CF obtained the value will be stored in the existing database. Testing result get 88.75% for accuracy. Key words Certainty factor, Rule-Based Expert System, Schizophrenia